Communication strategies in written text among basic learners of Japanese language: a case of Universiti Putra Malaysia’s students - Tajuddin, Farah; Mamat, Roslina; Abdul Halim, Hazlina; Ang, Lay Hoon; Abdul Rashid, Roswati; Jalaluddin, Ilyana (Faculty of Modern Languages and Communication, University of Putra, 2013)
The inability to fully express one’s intended meaning is fairly understandable for second language learners. It becomes more challenging in the case of foreign language whereby the language is not commonly used in the natural environment of the learner. Foreign language learners adopt several strategies in overcoming language difficulties in their communication. For students, it is equally important that they are able to convey their message in both oral and written texts. This paper exemplifies the Communication Strategies (CS) employed by Japanese language learners in their written texts. The participants in this study consisted of two groups, namely low-proficiency and highproficiency learners. The data was gathered through a writing task which was administered to the learners during the second half of the semester. Data later was analysed using Dornyei and Scott (1997) taxonomy of communication strategies. The findings showed that both proficiency learners displayed the employment of CS in different sequential orders. Low proficiency learners tend to rely on their L1 through code-switching more than the high-proficiency learners. Low proficiency learners also displayed higher reduction strategies such as topic avoidance due to their inadequate knowledge of the target language. The findings also show that task-type does influence the employment of CS, although the choice of CS seems to depend on the topic given in the task.